“Efecto de la altura de corte en el rendimiento de arroz de soca, variedad pairona, en el distrito de cacatachi – Bajo mayo” - López Reátegui, Talía Elizabeth (2005)
The present titled work "Effect of the court height in the yield of soca rice, · variety Capirona, in the District of Cacatachi - Low May" he has as objective to Determine the good height of court in the handling of soca of the rice variety Capirona, in the Valley of the First floor May and to determine the relationship benefit-cost of the treatments in study. The present investigation work was developed in the 1 am founded of the Farming Miguel Alexandria Tello, located in the Sector Chupishiña, in the high part of the Valley Low May; with the patronage of the ONG "URKU Amazon Studies." Likewise the Statistical Design of Blocks was used Randomizados Completely (DBCR) with six treatments (you cut to: 3; 6; 9 12; 15 and 20 cm) and four repetitions. The results demonstrated that the court height to 9 cm reached the maximum yield with 5 727 Kg/ha being proven that the court height affects to the yield of the soca of the rice; likewise a net profit of productlon of S was reached /. 3 207, 12 new and a relationship benefits cost of 1,75 indicating earnings of 0,75 suns for each alone one invested. The effect obtained on the yield was attributed to the component weight of grains, when being a highly significant lineal correlation among these. Also one presumes that the uniformity in the floración and vigor is related to the position of the yolks, being those that are in the entrenudos but high the most precocious; and that these impact in a smaller weight of grains and in losses of the . yield for on maturation. They were not significant effects of the court height in the variables: plant height, macollas number, number of cobs neither longitude of cobs. The soca cultivation reached its crop maturity to the 90 days after the cut of the main cultivation.